Comparing European workers. Part A - Brady, David, 1972- (Bingley, U.K. : Emerald, 2011)
Whether criticized or praised, European labor markets have been well-known for their social democracy and corporatism, and purported rigidities and inefficiencies. European labor markets have always stood out for supposedly providing workers more security and equality and/or being unable to foster job growth and flexibility. This volume places the labor markets, workplaces, jobs and workers of Europe in comparative perspective. It focuses on the politics, economics, sociology, and history of work and workers in Europe. Authors contribute a variety of methodological and theoretical perspectives, with papers that push the boundaries of evidence and argument. In order to place European workers in comparative perspectives, the volume features articles that analyze specific European countries, industries and firms, analyze Europe as one of a few cases, and analyze many European countries within a cross-national sample. It contains both qualitative and quantitative studies as well as explicitly theoretical work, and compares contemporary patterns and the recent history of European workers with other models of work worldwide.
Introduction / David Brady -- Reexamining the relationship between flexibility and insecurity / Andrew S. Fullerton, Dwanna L. Robertson, Jeffrey C. Dixon -- Work values and job rewards among European workers / Michael Wallace, Travis Scott Lowe -- The Islamic making of a capitalist habitus / Cihan Tugal -- Explaining cross-national variation in wage inequality / Vincent A. Mahler -- Testing the fat and mean thesis / Kevin T. Leicht, David Brady -- Cross-national patterns in individual and household employment and work hours by gender and parenthood / Joya Misra, Michelle J. Budig, Irene Boeckmann -- Domestic and international causes for the rise of pay inequality in OECD nations between 1980 and 2000 / Miriam A. Golden, Michael Wallerstein.
Print version record
Keywords: Social Science -- Sociology -- General; Business & Economics -- Labor; Social Science -- General; Sociology: work & labour; Sociology; Labor market -- Europe